Is There a Place for Popular Adult Education in the Managerial University? - Juha Suoranta (European Journal for Research on the Education and Learning of Adults, 2023)
This article studies the possibilities of reclaiming and revitalising popular adult education in Finland’s neoliberally driven managerial university and addresses the place for popular adult education in it. In Finland, popular adult education has been taught at a university level since the 1920s. Currently, it has a marginal position in academia. This descriptive case study ponders the role of teaching popular adult education in Finnish universities and describes the pilot program on popular adult education organised at Tampere University in 2020. The study suggests that popular adult education, even in managerial universities, can provide students and practitioners with meaningful knowledge and the means to build global humanity and a sustainable future. In conclusion, the article discusses the future of popular adult education and its role in the university.